Health- related quality of life for adult patient with chronic viral hepatitis B and C - Midhin, Adel; tawfeeq, Narmeen (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): This study aims to assess health related quality of life among Iraqi patients with chronic viral hepatitis B and C also to find out the relationship between health related quality of life and patients demographic characteristic and to design a new measurement scale for assessing QoL among viral hepatitis B and C patients which can be suitable to be adopted for Iraqi patients Methodology: A descriptive quantitative study is carried out at Gastroenterology and Hepatology Teaching Hospital from February, 1st, 2011 to August 30th 2011, Anon probability (purposive sample) of (100) chronic viral hepatitis B and C persons , who were clients of Gastroenterology and Hepatology Teaching Hospital / outpatient clinic for follow up. The data were collected through the use of semi-constructed questionnaire, which consists of three parts (1) demographic data form that contains (10) items (2) form medical information that contains of (7) items and (3) main domains of the quality of life which contains six main domains: physical, psychological, level of independence, social, environmental, spiritual domain. Content validity was determined by a panel of experts in different specialties. Reliability of instrument was determined by the use of test–retest approach through the pilot study. The data were described statistically and analyzed through use of the descriptive and inferential statistical analysis procedures. Results: The findings of the presented study indicate that the chronic viral hepatitis B and C affect the quality of life domains. There is a non-significant relationship between socio-demographic characteristic and quality of life domains. The study concludes that the chronic viral hepatitis B and C are most common occurring among persons in urban residential area than in those in rural. chronic viral hepatitis B and C are most common in male than in females, chronic viral hepatitis B and C are most common in married than in unmarried, chronic viral hepatitis B & C are most common in non-drink alcohol than in drink, chronic viral hepatitis B and C are most common in low level education than other, chronic viral hepatitis B and C are most common in low socioeconomic status. Recommendations : the study recommended An intensive comprehensive wide population-based ( national level) studies could be conducted to assess the chronic viral hepatitis B and C patients quality of life also Health oriented mass media approach should be employed by the Ministry of Health to increase population knowledge and awareness about the route of transmission and risk factor of chronic viral hepatitis B & C and Involving both governmental and non-governmental organizations in national health promotion campaign